Letter (copy) : Proposed deputation - Citrine, Walter, 1887-1983
011-0143-001 WMC/KMS/296 Secretary's. 10th February, 1937. Mr. G.W. Jones, 3, Hale End Road, E.17. Dear Mr. Jones, I have considered your letter of the 4th instant, suggesting that I should receive a deputation of the Trade Unionists who recently visited Spain as they have certain suggestions to a make as to means of helping the Spanish comrades. Whilst I do not wish to stand on ceremony I have to point out to you that it is a practice of the General Council to insist that representations from individual Trade Unionists shall be made through their Unions. A long experience has shown that this is infinitely the best course to take. Naturally I appreciate the desire of yourself and your colleagues to help in a practical way to assist the Spanish comrades in their struggle to maintain Democracy, and it would be very helpful to me in giving further consideration to our request for deputation, if you would be good enough to indicate in writing the proposals which the deputation have in mind. Yours fraternally, General Secretary. 292/946/11/143